Efek hipoglikemik cookies campuran tepung suweg dengan tepung garut - Henricus Totok Yulianto; Dwiyati Pujimulyani; Wisnu Adi Yulianto (LPPMPK- Universitas Muhammadiyah Cileungsi, 2023)
From 7.0% in 2007, to 6.9% in 2013, to 8.5% in 2018, and even to 21.3 million in 2030, the frequency of people with diabetes mellitus increases by 5.7% annually. In order to create mixed cookies with a low glycemic index that panelists prefer, this research mixes suweg flour and arrowroot flour. In this procedure, prepared and unprepared treatments are both used. Chemical properties (moisture content, protein content, total sugar content, and starch content), resistant starch (RS) flour, the amount of fiber in mixed cookies, the level of cookie choice among panelists, and volunteer blood glucose levels were all examined. to calculate the glycemic index of the biscuits. Based on a study of blood glucose levels in connection to the glycemic index, the sample cookies were rated as having a low GI (55) and had a glycemic index between 54.68 and 31.40. These cookies are a suitable diabetic diet food because they have a low glycemic index (55), resistant starch, and an adequate quantity of dietary fiber